CHILDREN'S CONCERNS AND FAMILY LAW CONFLICTS IN THE CIVIL REALM - Kumala, Brik; Sipayung, Parlin Dony; Renaldy, Rendy; Januri; Alqadri, Dinar; Maulidiana, Lina (Fakultas Hukum Universitas Kristen Indonesia Paulus, 2024)
In light of Law no. 35 of 2014 concerning Child Protection and its application in Case Number 300/Pdt.G/2022/PA.Tg., this study aims to examine the regulation of children's hadhanah rights after divorce. Finding out how the law protects children's rights after a divorce and the obstacles to implementing such protection is the goal of this study. Normative research using a legislative approach and content analysis is the research technique used. Case Number 300/Pdt.G/2022/PA.Tg-related court records and secondary data pertaining to the Child Protection Law will be gathered and analysed. With an emphasis on the maintenance of children's hadhanah rights after a divorce, this study seeks to enhance comprehension of legislative provisions and their implementation in court practice. A solid legislative foundation for safeguarding children's rights after a divorce, with the primary focus being on the child's best interests, is provided by the Child Protection Law, according to the study. As shown in Case Number 300/Pdt.G/2022/PA.Tg., this concept is put into reality by the courts in order to make fair judgements about child custody and maintenance in order to protect the well-being of children after a divorce. But this case study also shows that there are problems with the law's implementation, such as how to determine whether parents can afford it and what the kids need.